Financial Capability Formation and the Variables that Effect It with Respect to Canadian Consumers (International Journal of Applied Research in Management and Economics, 2021)
With the ascent of money, services provided in the financial systems of different economies have extended the hand of consumers on numerous commodities other than for current consumption but also for future consumption. It is a financially capable individual who is able to make informed financial decisions and understand the use and management of money. In this paper, we argue that not only the individual’s income, education, and age are significant in predicting financial capability but also his or her financial literacy, tangible assets, retirement plans and even debts and liabilities. By construction of a scoring mechanism based on behavioral and quantitative responses in a cross-sectional survey, we found that thirty percent of the variation in the financial capability index is explained by the parameters whereas the household income was found to be an insignificant parameter.